Manipulatif Tantrum: Strategi untuk Mewujudkan Keinginan Anak - Yulia, Resti; Suryana, Dadan; Safrizal, Safrizal (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
This study aims to describe the motives for tantrum behavior in child X in Jorong X, Solok Regency. This study uses a qualitative case study model. The case study model was chosen because this study focused on individual cases, namely the case of tantrum children. The location of this research was conducted in Jorong X in Solok Regency. The research informants were selected by purposive sampling technique with the consideration that the subject was chosen according to the research objectives. Based on this technique, five informants were obtained. The data collection procedure was carried out in three ways, namely open interviews, non-participant observation, and documentation. The data obtained from the collection techniques were analyzed by referring to the Miles and Huberman model which consists of four steps, namely data collection, coding, and sorting of data which are summarized in data reduction, data display, and concluding. Furthermore, guaranteeing the validity of the research data was carried out by using the triangulation technique, namely by combining three data collection methods. The results showed that tantrum behavior characterized by self-harm is a way for child X to make his wishes come true. The emergence of this behavior is supported by the response of parents who are more directing to a permissive pattern to always grant children's requests.